An arc-sequencing algorithm for intensity modulated arc therapy - Shepard, D. M.; Cao, D.; Afghan, M. K. N.; Earl, M. A. (Medical physics (Lancaster), 2007)
Intensity modulated arc therapy (IMAT) is an intensity modulated radiation therapy delivery technique originally proposed as an alternative to tomotherapy. IMAT uses a series of overlapping arcs to deliver optimized intensity patterns from each beam direction. The full potential of IMAT has gone largely unrealized due in part to a lack of robust and commercially available inverse planning tools. To address this, we have implemented an IMAT arc-sequencing algorithm that translates optimized intensity maps into deliverable IMAT plans. The sequencing algorithm uses simulated annealing to simultaneously optimize the aperture shapes and weights throughout each arc. The sequencer enforces the delivery constraints while minimizing the discrepancies between the optimized and sequenced intensity maps. The performance of the algorithm has been tested for ten patient cases (3 prostate, 3 brain, 2 head-and-neck, 1 lung, and 1 pancreas). Seven coplanar IMAT plans were created using an average of 4.6 arcs and 685 monitor units. Additionally, three noncoplanar plans were created using an average of 16 arcs and 498 monitor units. The results demonstrate that the arc sequencer can provide efficient and highly conformal IMAT plans. An average sequencing time of approximately 20 min was observed.